STUDI DESKRIPTIF SIKAP KESIAPSIAGAAN BANJIR ANAK SD DITINJAU DARI SEGI ETNIS DI DAS KOTA BENGKULU - Dalifa, Dalifa; Agusdianita, Neza; Karjiyati, V.; Wurjinem, Wurjinem (ATTA`DIB, 2021)
The descriptive study in this research describes the flood disaster preparedness attitude of children in the Bengkulu City River Basin. The method used in this research is descriptive qualitative method. The results showed that in theory, children already understood the steps that should be taken before a flood occurs, during a flood and after a flood. However, if a flood occurs, there are still children who do not heed the flood disaster preparedness protocol. Like playing and bathing in a puddle. Further research is needed to provide good understanding and awareness so that children not only know but can properly practice flood disaster preparedness when a flood occurs.